First available biosimilar monoclonal antibodies - Zh. I. Avdeeva; A. A. Soldatov; N. A. Alpatova; V. P. Bondarev; Yu. V. Olefir; V. A. Merkulov; V. D. Mosyagin; N. V. Medunitsyn (Биопрепараты: Профилактика, диагностика, лечение)
The review deals with the issues related to the special aspects of the development of the first available similar biopharmaceuticals/biological analogues («biosimilars») based on monoclonal antibodies. In June 2013 the Committee for Medicinal Products for Human Use (CHMP) of the European Medicines Agency (EMA) approved for licensing Remsima and Inflectra which are biosimilars of the brand-name product Remicade® (infliximab). The review describes the general principles of the development of the mentioned biosimilars. It highlights the features of the quality assessment studies, including characterization of the physical and chemical properties, specific biological activity, as well as comparative preclinical and clinical trials confirming the similarity of the candidate and the brand-name (reference) product. The review provides with the analysis of the results of comparative studies to assess the clinical relevance of the differences detected at the stage of quality assessment. The data substantiating the possibility of extrapolating the results obtained in clinical trials, against the approved standards for the brand-name product is provided.